The role of governance networks in building metropolitan scale. Issue 2 (3rd April 2018) - Nelles, Jen; Gross, Jill Simone; Kennedy, Loraine
ABSTRACT: The role of governance networks in building metropolitan scale – Territory, Politics, Governance . The broad aim of this comparative study is to examine the relationship between governance networks and the emergence (or lack thereof) of metropolitan scales through an analysis of metropolitan development-policy processes. It explores the characteristics and substance of policies that purport to be metropolitan in scope through a set of six case studies of global city-regions lacking a formal metropolitan-scale government: Berlin, Delhi, New York, Paris, Rome and Shenzhen. This is done to obtain a better sense of the networks, strategies and approaches used in various contexts to tackle boundary-spanning issues in regions. Three paired case studies analyse what interests and actors were involved, how central each actor was to the policy process, and what territorial scales and interests dominated to identify commonalities across cases and to look for evidence of the emergence of new actors in metropolitan policy-making and of political rescaling.